Lewd looks : American sexploitation cinema in the 1960s - Gorfinkel, Elena (University of Minnesota Press, 2017)
One of the most fascinating phenomena of 1960s film culture is the emergence of American sexploitation films--salacious indies made on the margins of Hollywood. Hundreds of such films were produced and shown on both urban and small-town screens over the course of the decade. Yet despite their vital importance to the film scene, and though they are now understood as a gateway to the emergence of publicly exhibited hardcore pornography in the early 1970s, these films have been largely overlooked by scholars. Defined by low budgets, quick production times, unknown actors, strategic uses of nudity, and a sensationalist obsession with unbridled female sexuality, sexploitation films provide a unique window into a tumultuous period in American culture and sexual politics. In Lewd Looks, Elena Gorfinkel examines the social and legal developments that made sexploitation films possible: their aesthetics, their regulation, and their audiences. Gorfinkel explores the ways sexploitation films changed how spectators encountered and made sense of the sexualized body and set the stage for the adult film industry of today. Lewd Looks recovers a lost chapter in the history of independent cinema and American culture--a subject that will engross readers interested in media, sexuality, gender, and the 1960s. Gorfinkel investigates the films and their contexts with scholarly depth and vivid storytelling, producing a new account of the obscene image, screen sex, and adult film and media.